Risk of PTSD in Service Members Who Were Fired Upon by the Enemy is Higher in Those Who Also Returned Fire. Issue 9 (1st September 2014) - McLay, Robert N.; Mantanona, Christy; Ram, Vasudha; Webb-Murphy, Jennifer; Klam, Warren; Johnston, Scott
ABSTRACT: An unusual characteristic of the recent wars in Iraq and Afghanistan is that, because of attacks by snipers and improvised explosive devices (IED), many U.S. service members may come under attack without having exchanged fire. It was hypothesized that this would be associated with greater severity of post-traumatic stress disorder (PTSD) symptoms. The severity of self-reported symptoms of PTSD and depression were examined among service members who reported being shot at or attacked by an IED, those who had these experiences but who also shot at the enemy, and those who reported neither experience. Results showed that those with neither exposure reported the lowest symptom severity, but, contrary to expectations, service members who had been attacked but not shot at the enemy had less severe symptoms than those who had exchanged fire. This may support findings from earlier generations of veterans that shooting at or killing the enemy may be a particularly traumatic experience.